Zygophyllum album leaves extract prevented hepatic fibrosis in rats, by reducing liver injury and suppressing oxidative stress, inflammation, apoptosis and the TGF-β1/Smads signaling pathways. Exploring of bioactive compounds using HPLC–DAD–ESI–QTOF-MS/MS - Feriani, Anouar; Tir, Meriam; Gómez-Caravaca, Ana María; del Mar Contreras, María; Taamalli, Amani; Segura-Carretero, Antonio; Ghazouani, Lakhdar; Mufti, Afoua; Tlili, Nizar; El Feki, Abdelfattah; Harrath, Abdel Halim; Allagui, Mohamed Salah (Inflammopharmacology, 2020)
Zygophyllum album is traditionally used against many illnesses, such as liver disease. The present study investigated the bioactive compounds in methanol extract of Z. album (MEZA) using HPLC–DAD–ESI–QTOF-MS/MS and explored its possible antioxidative, anti-inflammatory, anti-apoptotic, and hepatoprotective effect. Twelve phenolic compounds were identified; isorhamnetin-3- O -rutinoside being the main one was the main composite (144.6 mg/100 g dm). Results showed that MEZA reduced significantly the biochemical markers (AST, ALT, LDH and ALP), and the hepatic oxidative stress indicators (MDA, PC, SOD, CAT, and GPx) in deltamethrin (DLM)-treated rats. Moreover, MEZA limited the inflammatory responses through downregulation of NF-κB gene, which suppressed the production of proinflammatory cytokines (TNF-α, IL-1β, IL-6). Furthermore, Z. album reduced DLM-induced apoptosis by attenuating caspase 3 and p53 mRNA activation. MEZA treatment also alleviated upregulation of α-SMA, type I collagen, and TGF-β1 mRNA in the liver. The possible antifibrotic effect of MEZA was clearly demonstrated by the histopathology examination, using Masson’s Trichrome and Sirius Red stainings. Therefore, the current study suggested that the bioactive compounds of Z. album possessed antifibrotic effect against DLM-induced hepatic fibrosis, by protecting liver tissue, and inhibiting oxidative stress, inflammation, apoptosis and the TGF-β1/Smads signaling pathways.